COVID-19 pandemic: A wake-up call at science-policy-society to work towards a livable future - Feyen, Jan (Maskana, 2021)
The year 2021 is nearing its end when the online version of the journal MASKANA 12(2) is published. 2021, means that already one-fifth of the 21st century has passed. Since 2000 raised the world population from 6.1 to 7.9 billion, or 29.5%. Different models predict that the world population in 2030, the year that the world leaders in Glasgow (UK) during the GOP26 meeting agreed to limit global warming to 1.5°C, will increase to 8.5 billion. Wonder if the world possesses the capacity to secure food, given the continuing exponential growth of the population, and at the same time will be able to limit the warming up of the planet by 1.5°C? According to the yearly study of FAO (Food and Agriculture Organization of the United Nations) on the state of food security increased the number of people experiencing undernourishment since 2014, and today the world experiences an unprecedented setback in its hunger eradication effort. The major drivers behind the decline in food security and nutrition are according to FAO: conflict, climate variability and extremes, and economic slowdowns and downturns. The impacts the people experience are exacerbated by the levels of inequality in terms of income, productive capacity, assets, technology, education and health. The COVID-19 pandemic has been an additional factor that put the world off track to ending world hunger, malnutrition, climate change, immigration, that the rich are getting richer, and the poor are becoming poorer, among other phenomena of inequality. Parallel to these evolutions, democracy worldwide is in decline. According to IDEA (International Institute for Democracy and Electoral Assistance), is the trend of democratic erosion ongoing since 2006 and is today worse than ever before.